Comparison of the Effects of Two Types of Exercise on Blood Glucose Levels and Anti-diabetics Tablets Used by People with Type II Diabetes - L Yekkeh Fallah; H Azimi; T Sadeghi (Iran University of Medical Sciences, 2014)
Abstract :   Background & Aim: Diabetes can't be cured, but it can be controlled by other ways such as safe exercise (Yoga- walking ...) and balanced diet. The aim of this study was to compare the effects of a one -month regular yoga and walking exercise on blood glucose level and amount of anti-diabetics tablets used by people with type II diabetes.   Material & Methods: This quasi-experimental study was conducted on 60, 30-55 year old female and male volunteers with diabetes. The Participants were randomly assigned into 3 groups of yoga, walking and control. Yoga and walking group exercised for 45 minutes daily during a one month period. All of Participants completed the questionnaire for 2 times, before and after intervention. Patients were tested twice (before and after intervention) for fasting blood glucose by glucometer (ZD) (GM300). Data related to fasting blood glucose and the number of anti-diabetic tablets and sex were analyzed by Chi-square test and one-way ANOVA using SPSS win (v.16).   Results: Reduction of fasting blood glucose was significant at the end of intervention in yoga group (p=0 /016). However, it was not significant in walking group (p=0/054). There was no significant difference between the number of anti-diabetic used tablets before and after intervention (p > 0/05). There was significant differences in fasting blood glucose levels of the 3 groups after intervention according to repeated measurement (p<0.05).   Conclusion: According to the findings, one month of yoga and walking exercise is effective in reducing fasting blood glucose in people with type II diabetes. Although yoga was more effective in reducing fasting blood glucose, but it did not make a significant reduction in anti-diabetics used tablets . A same study with more duration of intervention and larger sample size is recommended.